A highly conserved sRNA downregulates multiple genes, including a σ54 transcriptional activator, in the virulence mode of Bordetella pertussis - Minji Sim; Jeffers Nguyen; Karolína Škopová; Kyungyoon Yoo; Chin-Hsien Tai; Leslie Knipling; Qing Chen; David Kim; Summer Nolan; Rawan Elaksher; Nadim Majdalani; Hernan Lorenzi; et al. (mBio)
ABSTRACT Bacterial small non-coding RNA (sRNAs), together with the RNA chaperone Hfq, post-transcriptionally regulate gene expression by affecting ribosome binding or mRNA stability. In the human pathogen Bordetella pertussis, the causative agent of whooping cough, hundreds of sRNAs have been identified, but their roles in B. pertussis biology are mostly unknown. Here we characterize the Hfq-dependent sRNABpsA, whose level is dramatically higher in the virulence (Bvg+) mode. We show that transcription from a σA-dependent promoter yields a long form of 190 nucleotides (nt) that is processed by RNase E to generate a shorter, more stable form (BpsA-S) of 67 nt. The transcript also encodes a small protein of 32 amino acids. Using RNA-seq and real time PCR, we identify 91 genes whose expression significantly increases in the absence of BpsA. Seventy contain sequences at/near their ribosome binding sites that are complementary to single-stranded regions (site 1 or 2) of BpsA-S. Identified genes include those encoding multiple transporters and three transcriptional regulators. Using a lacZ translational reporter system, we demonstrate that BpsA-S directly represses one of these genes, BP2158, a σ54-dependent transcriptional regulator, suggesting Bvg+ mode repression of a σ54 regulon. We find that the BpsA-S region containing sites 1 and 2 is 100% conserved throughout various Betaproteobacteria species, and BpsA-S target sites are often conserved among the homologs of the predicted B. pertussis target genes. We speculate that BpsA-S regulation represents a conserved process that fine-tunes gene expression in the Bvg+ mode of B. pertussis and perhaps under other conditions in related bacteria.IMPORTANCERegulation of gene expression involves controlling transcription, translation, and transcript degradation. sRNAs with short sequences complementary to an mRNA sequence are involved in post-transcriptional regulation by aiding or interfering with either ribosome binding or nuclease attack. In the human pathogen Bordetella pertussis, the causative agent of whooping cough, hundreds of sRNA have been identified, but their functions remain largely unknown. We have characterized an sRNA that is abundant in the virulence mode of B. pertussis and serves to downregulate multiple genes, including transcriptional regulators and various transporters. We demonstrate that this sRNA directly represses a transcriptional factor, suggesting that it influences the regulation of specific B. pertussis regulons. The high conservation of this sRNA and its targets within Betaproteobacteria suggests a conserved pathway for gene regulation.